Respostas

  • Usuário do Brainly
2014-08-15T01:58:07-03:00
A) Temos que, x^2-14x+24=0.

Vemos que, \Delta=(-14)^2-4\cdot1\cdot24=100.

Logo, x=\dfrac{14\pm10}{2}, ou seja, x'=12 e x''=2


b) Temos x^2-6x+9=0

Assim, \Delta=(-6)^2-4\cdot1\cdot9=0.

Logo, x=\dfrac{6}{2}=3, ou seja, x'=x''=3.


c) Temos a equação x^2-18x+72=0.

Observe que \Delta=(-18)^2-4\cdot1\cdot72=36.

Assim, x=\dfrac{18\pm6}{2}, isto é, x'=12 e x''=6.

d) Por fim, temos x^2+2x-3=0.

Notemos que, \Delta=2^2-4\cdot1\cdot(-3)=16.

Portanto, x=\dfrac{-2\pm4}{2}, isto é, x'=1 e x''=-3.